Chronic N-acetylcysteine administration prevents development of hypertension in N(omega)-nitro-L-arginine methyl ester-treated rats: the role of reactive oxygen species - Rauchová, Hana; Pechánová, Olga; Kunes, Jaroslav; Vokurková, Martina; Dobesová, Zdenka; Zicha, Josef (Hypertension research, 2005)
The aim of this study was to evaluate the production of superoxide anions as well as their role in the induction and/or maintenance of high blood pressure in rats with N(omega)-nitro-L-arginine methyl ester (L-NAME)-induced hypertension. In the preventive study, we compared adult Wistar rats treated with L-NAME for 4 weeks with L-NAME-treated rats that were simultaneously given N-acetylcysteine (NAC) in their drinking water. Basal blood pressure, superoxide production, conjugated dienes concentration and NO synthase (NOS) activity were measured at the end of the experiment. Chronic NOS inhibition by L-NAME treatment increased blood pressure, enhanced superoxide production in the aorta and elevated the concentration of conjugated dienes in the heart and kidney. All these changes were prevented by simultaneous NAC administration, which augmented NOS activity in L-NAME-treated rats. In the therapeutic study, the effects of chronic NAC treatment were studied in rats with established hypertension which developed during 4 weeks of L-NAME administration. The blood pressure effects of chronic NAC treatment in established L-NAME hypertension were only moderate, although this treatment also restored NOS activity and lowered conjugated dienes in the heart and kidney. Since chronic NAC treatment had better preventive than therapeutic effects, it seems that reactive oxygen species play a more important role in the induction than in the maintenance of L-NAME hypertension.
Keywords: Spin Labels; Animals; hypertenze; Antioxidants; Rats, Wistar; lékové interakce; Drug Interactions; Enzyme Inhibitors; aorta; Nitric Oxide Synthase; cyklické N-oxidy; Reactive Oxygen Species; spinové značení; acetylcystein; Hypertension; NG-Nitroarginine Methyl Ester; Male; NG-nitroargininmethylester; inhibitory enzymů; synthasa oxidu dusnatého; antioxidancia; reaktivní formy kyslíku; krysa rodu Rattus; Aorta; zvířata; mužské pohlaví; Rats; Cyclic N-Oxides; potkani Wistar; Acetylcysteine